Moldify: 2022 terminal year end report - Benedicto, Stephanie Francisco (Animo Repository, 2022)
Moldify was a result of a series of brainstorming and research sessions. My team and I wanted to develop a product that targets the plant-titos and plant-titas in our country. As this idea seems to be seasonal and cannot be sustained in the long run, we thought of making it more diversified and versatile; the idea led to pottery clay kits. Instead of just making plant pots out of clay, why not make something more out of it such as trinkets, pen holders, and a whole lot more. Since the clay used to make pottery requires firing, the team chose to switch it to air-dry clay. Thereafter, the dea to develop Moldify Air-Dry Clay Kits emerged. The business operated under the name Moldify which is a lexical brand name, and a wordplay on the words mold and modify. Mold means to knead or work a material into a desired consistency or shape while modify means to make basic or fundamental changes. President Combining these two words to form the portmanteau “Moldify'', a word that seeks to relate to the primary activity the customers will engage into with our flagship product — an all-in-one clay modeling kit. Mold means to knead or work a material into a desired consistency or shape while modify means to make basic or fundamental changes. Combining these two words to form the portmanteau “Moldify'', a word that seeks to relate to the primary activity the customers will engage into with our flagship product — an all-in-one clay modeling kit. Moldify Clay Kits are all-in-one kits with the materials needed for clay sculpting. A Moldify Kit includes 500g of Air-dry clay, 5 tubs of 20ml non-toxic Paint, 1 tub of 20ml Glossy Varnish, 1 Artist Sponge, 1 Rolling Pin, 5 pieces Sculpting tools, 1 Paint Brush, 1 Canvas Mat, thank you card, sculpting manual, and clay care card. The kits are packaged in a corrugated box enclosed with a logo printed box seal. As part of our diversification plan, we’ve introduced unbundled kits that allow the customers to purchase consumables either for making new clay projects or simply testing our products out.